New England Patriots - Frisch, Aaron, 1975- (Mankato, MN : Creative Education, 2011)
"An elementary look at the New England Patriots professional football team, including its formation in 1960, most memorable players, Super Bowl championships, and stars of today"--Provided by publisher.
Includes index.
Keywords: New England Patriots (Football team) -- History -- Juvenile literature